Taxonomy of Hohenbergia lanata Pereira & Moutinho, new collections with an amendment to its description - CAVALCANTE, BRAYAN P.; SOUZA, EVERTON H. DE; VERSIEUX, LEONARDO M.; MARTINELLI, ADRIANA P. (Anais da Academia Brasileira de Ciências, 2021)
Hohenbergia lanata Pereira & Moutinho is an endemic bromeliad of the State of Bahia (Brazil), occurring in an altitudinal transition forest between Caatinga dry woodland and Atlantic Forest. The type material was collected by Roberto Burle-Marx, who introduced it into cultivation in his gardens, but lacking the accurate provenance, only mentioning that it was collected between Milagres and Amargosa municipalities. It was later described by Pereira & Moutinho based on a cultivated specimen. In this work, we present new specimens found in natural populations in an area that coincides with the type locality description, enabling us to expand the description of the species, as well as to provide images of the living plants in the field, adding information about its habitat. The herbarium collections revision and the new population found in the field enabled us to propose an updated conservation status and to better characterize the habit, plant architecture, and to add new morphological comparisons and geographical distribution.Hohenbergia lanata Pereira & Moutinho is an endemic bromeliad of the State of Bahia (Brazil), occurring in an altitudinal transition forest between Caatinga dry woodland and Atlantic Forest. The type material was collected by Roberto Burle-Marx, who introduced it into cultivation in his gardens, but lacking the accurate provenance, only mentioning that it was collected between Milagres and Amargosa municipalities. It was later described by Pereira & Moutinho based on a cultivated specimen. In this work, we present new specimens found in natural populations in an area that coincides with the type locality description, enabling us to expand the description of the species, as well as to provide images of the living plants in the field, adding information about its habitat. The herbarium collections revision and the new population found in the field enabled us to propose an updated conservation status and to better characterize the habit, plant architecture, and to add new morphological comparisons and geographical distribution.